Innovative nanoparticle-based therapeutic strategies against glioblastoma multiform: a focus on enhanced delivery systems and efficacy - Wang, Kehan (Frontiers in Bioengineering and Biotechnology, 2025)
Glioblastoma multiforme (GBM) is an exceedingly aggressive primary brain neoplasm characterized by a dismal prognosis owing to its invasiveness, heterogeneity, and immunity to conventional therapies. Conventional therapies, including surgery, chemotherapy, and radiotherapy, encounter constraints due to tumor evasion and physiological obstacles, such as the blood-tumor (BTB) and blood-brain barriers (BBB), which impact the treatment of GBM. Nanotechnology is employed to augment the permeability of anticancer agents through these barriers, thereby improving treatment efficacy and minimizing toxicity. Lipid-based nanoparticles, such as nanostructured lipid carriers (NLCs) and solid lipid nanoparticles (SLNs), offer drug encapsulation, stability, and controlled release, whereas metal nanoparticles, including gold and silver, augment imaging and photothermal therapy efficacy. This review investigates the traversal of nano carriers across the BBB and BTB, emphasizing the significance of dimensions, charge, and surface functionality, while underscoring the potential of nanotechnology in managing GBM. Advancements in nanomedicine possess the capacity to create more efficacious therapeutic strategies, markedly improving patient outcomes in the management of GBM.